Kinetic laws of flavanoid extraction from mulberry leaves by extractant cavitation activation - Vitenko, Tetyana; Gumnitsky, Yaroslav (Publishing House of Lviv Polytechnic National University, 2011)
Mass transfer in a capillary-porous body-liquid extraction, on condition that an activated and unactivated extractant is used, has been experimentally investigated. The mechanism of the extraction process for extracting the desired components from mulberry leaves has been found. Experimental results are generalized on the base of a mathematical model that allows the process to be predicted when implementing it in practice. Експериментально досліджено масообмін при екстрагуванні в системі капілярно-пористе тіло – рідина за умов використання активованого і неактивованого екстраагента. Встановлено механізм процесу вилучення цільових компонентів з листя шовковиці білої. Експериментальні результати узагальнені на основі математичної моделі, що дає змогу прогнозувати процес під час його реалізації на практиці.
Кінетичні закономірності екстрагування флаваноїдів з листя білої шовковиці із застосуванням кавітаційної активації екстрагента
Keywords: extraction; cavitation activation; plant ran material; intensification; екстракційне вилучення; кавітаційна активація; рослинна сировина; інтенсифікація